2016
DOI: 10.1104/pp.16.00959
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Invertase Promotes Fruit Set under Heat Stress by Suppressing ROS-Independent Cell Death

Abstract: Reduced cell wall invertase (CWIN) activity has been shown to be associated with poor seed and fruit set under abiotic stress. Here, we examined whether genetically increasing native CWIN activity would sustain fruit set under long-term moderate heat stress (LMHS), an important factor limiting crop production, by using transgenic tomato (Solanum lycopersicum) with its CWIN inhibitor gene silenced and focusing on ovaries and fruits at 2 d before and after pollination, respectively. We found that the increase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 108 publications
9
56
0
Order By: Relevance
“…This suggested that acid invertase, rather than sucrose synthase, mainly contributed to the heat tolerance in TLY83, because of a greater decrease in sucrose synthase activity found in TLY83 than in LLY722 under heat stress (Figure a, A). Similar results were found in tomato plants, in which higher CWIN activity in anther and fruit caused a lower fruit abortion rate under heat stress compared with cultivars with lower CWIN activity (Li et al, ; Liu et al, ). Indeed, sucrose synthase is involved in the plant response to abiotic stress (González, Gordon, James, & Arrese‐Igor, ; Gordon, Minchin, Skot, & James, ; Kaur, Gupta, Kaur, Sandhu, & Gupta, ), whereas very few studies have been conducted under heat stress (Parrotta, Faleri, Cresti, & Cai, ).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This suggested that acid invertase, rather than sucrose synthase, mainly contributed to the heat tolerance in TLY83, because of a greater decrease in sucrose synthase activity found in TLY83 than in LLY722 under heat stress (Figure a, A). Similar results were found in tomato plants, in which higher CWIN activity in anther and fruit caused a lower fruit abortion rate under heat stress compared with cultivars with lower CWIN activity (Li et al, ; Liu et al, ). Indeed, sucrose synthase is involved in the plant response to abiotic stress (González, Gordon, James, & Arrese‐Igor, ; Gordon, Minchin, Skot, & James, ; Kaur, Gupta, Kaur, Sandhu, & Gupta, ), whereas very few studies have been conducted under heat stress (Parrotta, Faleri, Cresti, & Cai, ).…”
Section: Discussionsupporting
confidence: 72%
“…It is worth to note that high invertase activities have been reported in tomato reproductive organs, which enhance sucrose import and improve heat tolerance (Li et al, ). In this process, invertase inhibits PCD in a reactive oxygen species (ROS) independent manner by enhancing sucrose import and catabolism, heat shock proteins (HSPs) accumulation, and both auxin response and biosynthesis (Liu, Offler, & Ruan, ). However, very few researches address the function of invertase in heat tolerance in plants by focusing on the maintenance of energy homoeostasis, especially during the process of pollen pollination.…”
Section: Introductionmentioning
confidence: 99%
“…The transcript level of LIN5 is induced during ovary-to-fruit transition (Palmer et al, 2015). Increase in the invertase activity by silencing INHI promotes fruit set under heat stress (Liu et al, 2016). Examination of some sucrose hydrolysis gene expression revealed that the young fruitlets of both AtOR overexpression lines contained significantly higher LIN5 transcript and lower INH1 expression than M82 ( Figure 6) to correlate with enhanced fruit set and seed production.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that activity of the CWINs in apoplasm of phloem could facilitate phloem unloading of Suc and other resources and the generation of glucose (Glc) signal to activate or stimulate cell division and to block programmed cell death (PCD) (Wang and Ruan ; Palmer et al ). Indeed, we recently showed that elevation of CWIN activity improved tomato fruit set under heat stress by suppressing PCD (Liu et al ). It will be of major significance to identify the promoter elements and the interacting proteins or signaling molecules underlying the phloem‐specificity of these CWIN genes.…”
Section: Transcriptional Regulation Of Genes Underlying Carbon Partitmentioning
confidence: 99%